Cell polarity and morphogenesis - Lecuit, Thomas (Methods in cell biology, 2017)
Cell Polarity and Morphogenesis, the latest volume in the Methods in Cell Biology series, looks at cell polarity and morphogenesis. Edited by leaders in the field, this volume provides proven, state-of-art techniques, along with relevant historical background and theory, to aid researchers in efficient design and effective implementation of experimental methodologies.